Validation of general job satisfaction in the Korean Labor and Income Panel Study - Shin Goo Park; Sang Hee Hwang (Annals of Occupational and Environmental Medicine, 2017)
Abstract Background The purpose of this study is to assess the validity and reliability of general job satisfaction (JS) in the Korean Labor and Income Panel Study (KLIPS). Methods We used the data from the 17th wave (2014) of the nationwide KLIPS, which selected a representative panel sample of Korean households and individuals aged 15 or older residing in urban areas. We included in this study 7679 employed subjects (4529 males and 3150 females). The general JS instrument consisted of five items rated on a scale from 1 (strongly disagree) to 5 (strongly agree). The general JS reliability was assessed using the corrected item-total correlation and Cronbach’s alpha coefficient. The validity of general JS was assessed using confirmatory factor analysis (CFA) and Pearson’s correlation. Results The corrected item-total correlations ranged from 0.736 to 0.837. Therefore, no items were removed. Cronbach’s alpha for general JS was 0.925, indicating excellent internal consistency. The CFA of the general JS model showed a good fit. Pearson’s correlation coefficients for convergent validity showed moderate or strong correlations. Conclusion The results obtained in our study confirm the validity and reliability of general JS.